Kardiomiopati peripartum vs Kardiomiopati peripartum dengan preeklamsia: dari pendekatan biomolekuler hingga manajemen - Fahreza, Lufthi; Winato, Brigad Mahardika; Nugrahani, Annisa Dewi; Arianto, Steven (Jurnal Biomedika dan Kesehatan, 2024)
Peripartum cardiomyopathy (PPCM) is a potentially life-threatening pregnancy-related condition that typically occurs during the peripartum period. It is characterized by impaired function of the left ventricle and heart failure. Preeclampsia is recognized as a risk factor for PPCM and can coexist with this condition. However, there is limited available data that explains the variations in treatment approaches between cases of peripartum cardiomyopathy with and without preeclampsia. Hence, the objective of this study is to examine the distinctions between PPCM and PPCM accompanied by preeclampsia, encompassing their molecular, pathogenic, and pathophysiological aspects, as well as their treatment and management strategies. These factors could potentially play a role in influencing the treatment of patients diagnosed with peripartum cardiomyopathy. A thorough review of existing literature was conducted between June and August 2023. Articles were retrieved from medical databases including PubMed, EBSCOhost, Medline, SAGE, JSTOR, and ScienceDirect, utilizing keywords such as "Peripartum Cardiomyopathy," "PPCM," "Preeclampsia," "Biomolecular," and "Treatment." This study encompassed original articles written in either English or Indonesian, focusing on a ten-year time frame. Articles categorized as literature reviews, systematic reviews, and/or meta-analyses were excluded from consideration in this study. The Results of this review, In instances of PPCM accompanied by preeclampsia, the secretion of sFlt1 from the placenta is notably elevated compared to cases of PPCM alone. PPCM and PPCM with preeclampsia exhibit distinct pathogenic and pathophysiological characteristics. Patients with concentric left ventricular remodeling (PPCM with preeclampsia) may not derive the same degree of benefit from angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, or beta-blockers as those with eccentric left ventricular remodeling (PPCM without preeclampsia). The Conclusion of this review, PPCM and PPCM with preeclampsia are differentiated by underlying biomolecular factors, pathogenesis, and pathophysiology. Furthermore, they respond differently to treatment and have different approaches to management.